SHEAR RESISTANCE OF LONGITUDINAL SHEAR CONNECTION WITH GROUPS OF HEADED STUDS - Spremić, Milan; Marković, Zlatko; Dobrić, Jelena; Buđevac, Dragan (Journal of Applied Engineering Science, 2016)
The frequently applied solution for shear connection in steel and concrete precast composite structures is the discontinuous shear connection with a headed stud in group arrangement. Application of shear connection with headed studs in group arrangement and calculation of shear resistance for studs group in typical precast composite floor beam is presented. The possibility and feasibility of shear connection construction with headed studs in group arrangement was considered. It is shown that the shear connection in precast composite floor beams can be constructed with a group of four headed studs.
Keywords: shear connection; prefabricated composite beams; group of headed studs